2010
DOI: 10.1242/jcs.067686
|View full text |Cite
|
Sign up to set email alerts
|

Golgi-to-phagosome transport of acid sphingomyelinase and prosaposin is mediated by sortilin

Abstract: SummarySortilin, also known as neurotensin receptor 3 (NTR3), is a transmembrane protein with a dual function. It acts as a receptor for neuromediators and growth factors at the plasma membrane, but it has also been implicated in binding and transport of some lysosomal proteins. However, the role of sortilin during phagosome maturation has not been investigated before. Here, we show that in macrophages, sortilin is mainly localized in the Golgi and transported to latex-bead phagosomes (LBPs). Using live-cell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 50 publications
5
58
0
Order By: Relevance
“…Interestingly, loss of sortilin expression reduced the Ag-processing capacity in Sort1 2/2 DCs compared with WT DCs, the most effective APCs. In line with this observation, Wähe et al (19) described that sortilin is involved in the transport of lysosomal proteins in a Golgi-dependent route to phagosomes in macrophages. Upregulation of sortilin in macrophages was also detected during the process of mycobacterial killing (25), emphasizing its role in correct cell function during response to Ags.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, loss of sortilin expression reduced the Ag-processing capacity in Sort1 2/2 DCs compared with WT DCs, the most effective APCs. In line with this observation, Wähe et al (19) described that sortilin is involved in the transport of lysosomal proteins in a Golgi-dependent route to phagosomes in macrophages. Upregulation of sortilin in macrophages was also detected during the process of mycobacterial killing (25), emphasizing its role in correct cell function during response to Ags.…”
Section: Discussionmentioning
confidence: 69%
“…In this context, Herda et al (18) showed that cytotoxic T cells lacking sortilin produce less IFN-g and more granzyme A. In addition, Wähe et al (19) suggested that sortilin transports target proteins to phagosomes in macrophages. Combining sortilin's role as a proneurotrophin receptor in the CNS and its more recently described influence on several immune cell subsets, we were interested in its impact on inflammatory processes in the CNS.…”
mentioning
confidence: 99%
“…RAW 264.7 macrophages were grown in high glucose DMEM with 10% (vol/vol) heat inactivated FCS incubated at 37°C in a 5% (vol/vol) CO 2 atmosphere. BMMs were obtained as described before (40). M. bovis bacillus Calmette-Guérin expressing GFP and DsRed were kind gifts of Brigitte Gicquel (Institute Pasteur, Paris, France).…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages were pulsed with 1-μm beads and isolated after 15, 30, and 60 min of chase as described before (40).…”
Section: Methodsmentioning
confidence: 99%
“…It is a member of the Vps10p domain receptor family, characterized by a 10-bladed β-propeller that forms a cavity for binding of soluble ligands and a C-terminal cytoplasmic tail that contains sorting motifs responsible for subcellular distribution of the receptors (8)(9)(10). Sortilin exerts diverse cellular functions including intracellular sorting of proteins, such as acid sphingomyelinase, apolipoprotein B100 (apoB100), and PCSK9, as well as engaging in signaling as a coreceptor in cell surface receptor complexes (5)(6)(7)(11)(12)(13). Given the broad functional repertoire of sortilin, we hypothesized that it may affect atherogenesis beyond regulating plasma cholesterol levels.…”
Section: Introductionmentioning
confidence: 99%